(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In the period from 2013 to 2021 the clinic of Tashkent Medical Academy for examination and treatment were 138 patients with adrenal tumors. Simultaneous operations were performed in 18 patients, of whom 12 women and 6 men. A morphological study of adrenal tumors, we found: 50 - aldosteroma (33.3%), 19- pheochromocytoma (16.6%), 19 - adrenal cyst (16.6%), 50 - cortex adenoma (33.3%). Of these, 50% patients were with intsidentaloma (2 cortical adenoma and 1 adrenal cyst). Indications for simultaneous operations were a combination of adrenal tumors with cholelithiasis and umbilical hernia. At the same time in 12 (66.6%) patients simultaneously conducted operations - right-sided laparoscopic adrenalectomy, and laparoscopic cholecystectomy, in 3 patient (16.6%) - a left laparoscopic adrenalectomy and laparoscopic cholecystectomy and 3 (16.6%) patient’s after adrenalectomy surgery hernia repair is made to the type of allopath «on lay». In postoperative period complications were not observed. On the next day after surgery drains removed and all patients are activated. Average bed day was 4 ± 1,71. Thus, the analysis of these patients treatment results showed that the duration of surgery and hospital stay do not differ from similar parameters specific to patients with isolated surgical pathology. Treatment simultaneously several surgical diseases liquidate of need for repeated operations and its risk of possible complications. All of the above underscores the feasibility and cost-effectiveness of performing simultaneous operations in patients with concomitant surgical pathology.